Comparison of blood urea nitrogen level between weaned alpacas and llamas grazing cultivated pastures - Vivar H., Mery (2019)
The aim of this study was to compare the level of blood urea nitrogen (BUN) between weaned alpacas and llamas grazing cultivated pastures. It was used 63 alpacas and 64 llamas, both females and males, maintained for 21 days after weaning on cultivated pastures (association of Italian rye grass [Lolium multiflorum] and white clover [Trifolium repens]). The blood sample was taken on day 21 of the study before animals went for grazing. The chemical composition of the offered feed, BUN and the selectivity index (SI) were evaluated. The BUN determination was done by visible UV spectrophotometry with a commercial kit. The IS was determined between the botanical composition of the pasture and the botanical composition of feed consumed. The data were analyzed through the Student t test of two samples with equal variances. The chemical composition of the cultivated grass offered for dry matter, crude protein, crude fiber, ethereal extract and ash was 18.09, 16.30, 19.20, 1.43 and 6.60%, respectively. BUN values in alpacas and llamas were 19.04 ± 3.24 mg/dl (12.13 - 26.36 mg/dl) and 19.05 ± 3.93 mg/dl (8.80 - 25.69 mg/dl), respectively, without significant difference between species. The IS was neutral, and no selectivity was found in both species. It is concluded that BUN is similar between weaned alpacas and llamas grazing cultivated pastures and they did not show selectivity for consumption.